2016
DOI: 10.18632/oncotarget.9850
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-218 inhibits EMT, migration and invasion by targeting SFMBT1 and DCUN1D1 in cervical cancer

Abstract: Repeated infection with high-risk HPV is a major cause for the development and metastasis of human cervical cancer, even though the mechanism of the metastasis is still not completely understood. Here, we reported that miR-218 (microRNA-218) was downregulated in cervical cancer tissues, especially in metastatic cancer tissues. We found that miR-218 expression was associated with clinicopathological characteristics of patients with cervical cancer. MiR-218 overexpression inhibited Epithelial-Mesenchymal Transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 42 publications
3
49
0
Order By: Relevance
“…Previous studies have demonstrated that DCUN1D1 is upregulated in squamous cell carcinoma, and promotes non-small cell lung cancer progression and brain metastasis (27,28). Recently, Jiang et al (22) reported that miR-218 inhibited epithelial-mesenchymal transition, migration and invasion by targeting Scm-like with four mbt domains 1 and DCUN1D1 in cervical cancer. However, the regulatory mechanism of DCUN1D1 expression in cervical cancer has remained obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that DCUN1D1 is upregulated in squamous cell carcinoma, and promotes non-small cell lung cancer progression and brain metastasis (27,28). Recently, Jiang et al (22) reported that miR-218 inhibited epithelial-mesenchymal transition, migration and invasion by targeting Scm-like with four mbt domains 1 and DCUN1D1 in cervical cancer. However, the regulatory mechanism of DCUN1D1 expression in cervical cancer has remained obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-218 was reported to inhibit cervical cancer cell migration and invasion by targeting DCUN1D1 (22). However, whether DCUN1D1 is also regulated by other miRNA in cervical cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…EMT is tightly regulated by several internal and external stimuli that orchestrate the transition from an epithelial-like to a mesenchymal phenotype (15)(16)(17). EMT facilitates tumor cell invasiveness and metastatic capacity, and is thus a principal mediator of cancer progression and metastasis (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…One of the targets of miR-218 is LAMB3 with roles in cell migration and carcinogenesis of cervical cancer. Another study revealed that the expression of miR-218 can lead to EMT inhibition, migration and invasion by targeting pro-tumorigenic genes such as SFMBT1 and DCUN1D1 [69]. Recently, the expression of miR-218…”
Section: High-risk Hpv Infection Modulates Mirna Expression In Cervicmentioning
confidence: 99%